“One Nation under God?”: Ethnicity and Identity in Modern America - Gary D. German (Amnis)
This paper examines the sources of “Anglo-Saxonism”, the invention of English ethnicity and the manner in which the latter came to fuse with Protestant Christianity from the 16th century onwards in creating the notion of the WASP. We then go on to study the degree to which colonial American society and the institutions of the early American Republic were infused with this ideology. From there, the paper explores the factors which led to the decline of WASP ethnicity during the latter half of the 20th century. We conclude with a discussion of the political, social and demographic consequences of multiculturalism on American society and the possible socio-political models from which Americans will have to choose if a Balkanization of the United States is to be avoided in the future.